Internship Experience in Orthopaedics and Traumatology and its Impact on Becoming a Specialist - Kasch, Richard; Abert, Eva; Kolleck, Nina; Ghanem, Mohamed; Froehlich, Susanne; Hofer, André; Schulz, Arndt Peter; Wassilew, Georgi; Herbstreit, Stephanie (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Introduction The German practical year is the last clinical placement period during Medical School. However, it remains unclear how medical students evaluate the practical year in orthopaedics and traumatology (Orthopädie und Unfallchirurgie; O & U) and whether it has an impact on becoming an O & U specialist.Method We analysed data of 146 medical students (46,7% female) who completed the placement in O & U. From the evaluation, 37 items were included in the analyses. Participants who could imagine becoming an O & U specialist (O & U-Ja) following graduation were statistically compared to those who could not (O & U-Nein).Results Overall 123 (83.7%) trainees indicated that they would like to become an O & U specialist (O & U-Ja), 18 (12.8%) negated (O & U-Nein) and 6 (4.1%) were undecided. Groups did not differ for sex and age (sex: Chi² = 2.50, p = 0.114; age: F [1.93] < 1, p = 0.764). Group differences were found for practical orientation, independency, acquisition of anamnesis and diagnostics skills and problem-solving expertise with students who could imagine becoming an O & U specialist (O & U-Ja) giving the highest ratings.Discussion Evaluations of the last medical year are essential in order to continuously improve the internship experience and to attract students towards a certain medical field and, moreover, to post-graduate specialist training. Clinics and institutions who already emphasize on the factors derived from this evaluation, or are continuously working on improvement, might be more able to attract young professionals, since personnel acquisition is starting early in the medical field.Einleitung Das Praktische Jahr (PJ) ist die letzte Ausbildungsstation im Medizinstudium. Unklar ist sowohl die Praktikumswahrnehmung seitens der Medizinstudierenden als auch die Identifikation von Motivatoren für eine anschließende Weiterbildung in Orthopädie und Unfallchirurgie (O & U).Methode Wir analysierten die Angaben von 146 PJlern (46,7% weiblich), die ihr Tertial in O & U absolviert hatten. Aus der Evaluation flossen 37 Items in die Analyse ein. Die Teilnehmer, die sich nach ihrem PJ vorstellen konnten, auch die Weiterbildung in O & U zu absolvieren (O & U-Ja) wurden getrennt von denen analysiert, die dies verneinten (O & U-Nein) und miteinander verglichen.Ergebnisse Insgesamt gaben 123 (83,7%) PJler an, auch ihre Weiterbildung in O & U machen zu wollen (O & U-Ja), 18 (12,8%) verneinten dies (O & U-Nein), 6 (4,1%) waren noch unentschlossen. In Geschlecht und Alter unterschieden sich diese beiden Gruppen nicht (Geschlecht: Chi² = 2,50, p = 0,114; Alter: F [1, 93] < 1, p = 0,764). PJler mit einer positiven Einstellung zur Weiterbildung in O & U (O & U-Ja) evaluierten ihr Tertial bei Praxisbezug, Selbstständigkeit, Sicherheit in Anamnese und Diagnosefindung und klinischen Problemlösungsfähigkeiten signifikant besser.Diskussion Beurteilungen zur Zufriedenheit im Praktischen Jahr sind erforderlich, um diesen Studienabschnitt kontinuierlich zu verbessern und die Studierenden durch ein erfolgreiches PJ-Tertial für die Weiterbildung in diesem Bereich zu gewinnen. Womöglich werden Ausbildungsstätten, die die in dieser Evaluation gezeigten Faktoren bereits in der PJ-Ausbildung betonen, zukünftig eher in der Lage sein, den fachlichen Nachwuchs an sich zu binden, werden doch in der personellen Akquise die Weichen bereits sehr früh gestellt.
Keywords: orthopaedic surgery; traumatology; practical internship; medical student; training